2021
DOI: 10.3329/jsr.v13i2.49965
|View full text |Cite
|
Sign up to set email alerts
|

On the Sandor-Smarandache Function

Abstract: In the current literature, a new Smarandache-type arithmetic function, involving binomial coefficients, has been proposed by Sandor. The new function, denoted by SS(n), is named the Sandor-Smarandache function. It has been found that, like many Smarandache-type functions, SS(n) is not multiplicative. Sandor found SS(n) when n (≥3) is an odd integer. Since then, the determination of SS(n) for even n remains a challenging problem. It has been shown that the function has a simple form even when n is even and not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Islam et al [3] proved the results below. Lemma 1.1: SS(n) = n -2 if and only if n (  7) is an odd integer.…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…Islam et al [3] proved the results below. Lemma 1.1: SS(n) = n -2 if and only if n (  7) is an odd integer.…”
Section: Introductionmentioning
confidence: 62%
“…Later, the problem was studied to some extent by Islam, and Majumdar [6], who derived the expressions of SS(2mp), SS(6mp), SS(60mp), and SS(420mp), where p is an odd prime and m is any (positive) integer. Islam et al [3] subsequently found explicit forms of SS(6t), SS(12t), SS(18t), SS(42t), SS(30t), and SS(210t) for some particular cases of t. Later, Majumdar and Ahmed [7] extended the results of Islam et al [3] by considering all the possible cases involved in SS(210t). Recently, Islam and Majumdar [4] derived the expressions of SS(120m), SS(840m), SS(9240m), and SS(120120m) for some particular cases of m.…”
Section: Fig 11 a Tree Diagram Of Ss(n)mentioning
confidence: 90%
See 1 more Smart Citation
“…Some results related to the Sandor-Smarandache function are given in Majumdar [6]. The function was later studied in more detail by Islam and Majumdar [12], Islam, Gunarto and Majumdar [13], and more recently by [14] and [15]. The following result is also known about the Sandor-Smarandache function.…”
Section: Sandor-smarandache Functionmentioning
confidence: 99%